2019
DOI: 10.3390/cells8080811
|View full text |Cite
|
Sign up to set email alerts
|

Clues to Non-Invasive Implantation Window Monitoring: Isolation and Characterisation of Endometrial Exosomes

Abstract: Despite the significant advances in the last decades, low implantation rate per transferred embryo still remains a major concern in assisted reproductive techniques, highlighting a need to better characterize endometrial receptivity also by mean of specific biomarkers. Based on physiology and on the intimate contact with endometrium as the tissue of interest, in this study we developed and validated an optimized protocol that uses extracellular vesicles (EVs) recovered from uterine flushings and from a cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…UF samples were obtained by lavage of the endometrial cavity with 2.5 ml of sterile saline solution using a balloon hysterosonography catheter to avoid vaginal contamination. As previously reported, recovered volume may vary (from 0.8 to 1.8 ml in our series) ( Luddi et al , 2019 ). For EVs isolation, UFs were freshly processed to avoid freezing/thawing cycles.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…UF samples were obtained by lavage of the endometrial cavity with 2.5 ml of sterile saline solution using a balloon hysterosonography catheter to avoid vaginal contamination. As previously reported, recovered volume may vary (from 0.8 to 1.8 ml in our series) ( Luddi et al , 2019 ). For EVs isolation, UFs were freshly processed to avoid freezing/thawing cycles.…”
Section: Methodssupporting
confidence: 78%
“…In this study, we sought to determine the RNA content of EVs released in the uterine microenvironment in order to understand its potential value as a proxy of endometrial receptivity status. Purified EV populations containing exosomes have been previously isolated and characterized in uterine fluid ( Ng et al , 2013 ; Vilella et al , 2015 ; Luddi et al , 2019 ). Different protocols for their isolation have been assessed ( Vilella et al , 2015 ; Campoy et al , 2016 ) and the standard procedure by differential centrifugation was found as the best approach in terms of providing sufficient materials for proteomic and transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Proteome profiling of the uterine fluid that contains EVs have identified a panel of proteins that has specificity and sensitivity of 91.7% for distinguishing proliferative and receptive phase samples; the panel can also differentiate RIF non‐invasively with 91.7% specificity and 96.6% sensitivity 34 . In another study, EVs have been isolated from uterine flushes and cervical brush and characterized using molecular markers 112 . These EVs express putative endometrial markers, such as glycodelin A and receptors for oestrogen and progesterone, thus, confirming their endometrial origin, the levels of these markers vary by stage of the cycle 112 …”
Section: Endometrial Extracellular Vesicles In Diagnosticsmentioning
confidence: 99%
“…In the mare, little is known about the uterine EVs and their contribution to embryo-maternal interactions leading to successful pregnancy. Due to the very unique features of reproduction in equids, current results from other mammalian species such as mouse, sheep, bovine, pig or human [ 14 , 23 , 24 , 25 ], cannot be simply applied to horses. Studies in the mare have focused on EVs from follicular fluid and their miRNAs and protein cargo, as a possible new form of cell communication within the ovarian follicle [ 26 ].…”
Section: Introductionmentioning
confidence: 99%